Shamal's secret - Brown, Felicity; Theurer, Heather (New York : Harper Festival, 2010)
"Meet Shamal, a desert horse with remarkable strength and a mysterious past. When a young girl needs his help but resists it, Shamal must find a way to guide her to safety. Together they go on a journey that bonds them forever."-- p. [4] of cover.
Accelerated Reader AR
Keywords: Horses -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Horses -- Fiction; Animals, Mythical -- Fiction; Fantasy fiction